Efektivitas Limbah Serat Batang Sagu dalam Mengurangi Kadar Besi (Fe) pada Air Sumur - Yudhi Dwi Hartono; Yunita Eka Pratiwi (LP3M Universitas Muhammadiyah Kendari, 2022)
From the results of previous studies, the level of iron (Fe) in well water in Kendari City is above the quality standard. One method to reduce iron content in groundwater is using sago stem fiber. Sago stem fiber is used because the amount is quite abundant and is not utilized. This study aims to determine the effectiveness of the use of sago stem fiber in reducing iron in groundwater. The research method used was experimental in the laboratory to see the iron content in the water before going through filtration and after filtration with variations in the use of sago stem fiber as thick as 10 cm, 20 cm and 30 cm. Experimental results show that the use of sago fiber filtration can significantly reduce the iron content in groundwater, which is 1.4172 mg/L in a row to 0.0021 mg/L, 0.0018 mg/L, 0.0012 mg/L. The thicker the sago fiber used, the more effective it is in reducing iron content. After being filtered, the iron content in the well water used as a sample meets the standard for clean water, which is a maximum of 1 mg/L.